Development And Improvement Skills Preschool Education in Uzbekistan: Trends And Current State - Izzatoy Turdiyeva (Euro Asian Journal Publishing, 2024)
This article analyzes the activities of preschool educational institutions in Uzbekistan. It is noted that due to the creation of a healthy competitive environment among state and non-state preschool educational institutions in the republic, phased coverage of children with preschool education is being carried out
Keywords: state and non-state preschool educational institutions; quality of education; legal base; material and technical base